A question of courage - Darke, Marjorie; Lucas, Bill.; Keaney, Brian (Oxford Oxford University Press, 1990)
A young English seamstress becomes involved in the Suffragette movement before World War I.
Originall published as a novel in 1975.
Keywords: Suffragists -- Great Britain -- Juvenile drama; Women -- Suffrage -- Great Britain -- Juvenile drama; Women -- Suffrage -- Juvenile drama; England -- Social conditions -- Juvenile drama